Coordination-driven self-assembly of an iridium-cornered prismatic cage and encapsulation of three heteroguests in its large cavity1. Issue 21 (14th March 2015) - Singh, Nem; Jo, Jae-Ho; Song, Young Ho; Kim, Hyunuk; Kim, Dongwook; Lah, Myoung Soo; Chi, Ki-Whan
<x xml:space="preserve">Abstract</x> An iridium-cornered nanometer-sized prismatic cage has been synthesized and characterized which allows three planar heteroguest molecules inside its cavity.